Environmental justice organizations and the diffusion of conflicts over mining in Latin America. (June 2022) - Reeder, Bryce W.; Arce, Moises; Siefkas, Adrian
Highlights: Our spatial econometric analysis demonstrates that mining conflicts cluster in time and geographic space. Further analysis reveals Environmental justice organizations (EJOs) to be a primary driver of diffusion processes. Diffusion explains why some conflicts remain localized and fragmented, while others connect more actors, intensifying resistance. Abstract: Existing research has explored the factors affecting the likelihood of resistance to mining projects. These studies emphasize the geographic and firm-level characteristics of mining sites as well as the impact of these projects on the environment and community livelihoods. While making important contributions, the existing literature has failed to examine the contagion effects of conflicts over mining. Building on the literature on the diffusion of social movements, we argue that environmental justice organizations (EJOs) help diffuse mining conflicts through interpersonal networks involving individuals or organizations, organizational brokers as well as communication strategies through the mass media. Our spatial econometric analysis demonstrates that mining conflicts cluster in time and space and that EJO networks are the primary drivers of diffusion. The diffusion effects associated with EJOs help our understanding of local resistance to mining and represent an important pattern explaining the expansion of social conflicts in Latin America.